2016
DOI: 10.2147/ijn.s92257
|View full text |Cite
|
Sign up to set email alerts
|

Novel walnut peptide–selenium hybrids with enhanced anticancer synergism: facile synthesis and mechanistic investigation of anticancer activity

Abstract: This contribution reports a facile synthesis of degreased walnut peptides (WP1)-functionalized selenium nanoparticles (SeNPs) hybrids with enhanced anticancer activity and a detailed mechanistic evaluation of its superior anticancer activity. Structural and chemical characterizations proved that SeNPs are effectively capped with WP1 via physical absorption, resulting in a stable hybrid structure with an average diameter of 89.22 nm. A panel of selected human cancer cell lines demonstrated high susceptibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Cell viability was evaluated using MTT assays [ 45 ]. The cells were seeded in 96-well plates at a density of 4,000 cells per well and then treated with geridonin, paclitaxel, or oridonin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell viability was evaluated using MTT assays [ 45 ]. The cells were seeded in 96-well plates at a density of 4,000 cells per well and then treated with geridonin, paclitaxel, or oridonin.…”
Section: Methodsmentioning
confidence: 99%
“…The mitochondrial membrane potential was measured using JC-1 dye [ 45 , 47 ]. MGC 803 cells were seeded on glass coverslips and treated with geridonin, paclitaxel, or geridonin plus paclitaxel for 24 h. MGC 803 cells were then stained with 5 ÎŒg/mL JC-1 (Beyotime Biotechnology) at 37°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Walnut has extensive health-promoting functions, including antifungal [14], antitumor [14], antioxidant [13], anti-inflammatory [15], immune modulation [14], and antihypertensive properties [16]. Bioactive peptides are important protein fragments that have a wide range of pharmacological functions, such as anti-oxidative, anti-hypoxia, antimicrobial and immunomodulatory [17]. One animal study showed that oral administration of walnut extract had anti-fatigue effects and could significantly elevate exercise tolerance in mice [18].…”
Section: Introductionmentioning
confidence: 99%
“…(2016) who developed a method for the synthesis of walnut peptide (WP1)‐functionalized selenium nanoparticles (SeNPs) as an anticancer system. This delivery system improved peptide stability and increased the anticancer activity of SeNPs (Ren et al ., 2016).…”
Section: Improving Biological Activities Of Nut Peptidesmentioning
confidence: 99%